2017
DOI: 10.1177/1934578x1701200224
|View full text |Cite
|
Sign up to set email alerts
|

Raphanus sativus Sprout Causes Selective Cytotoxic Effect on p53-Deficient Human Lung Cancer Cells in vitro

Abstract: Raphanus sativus L. (Brassicaceae) is widely consumed in many different forms worldwide. Its sprouts, in particular, are commonly consumed as a health food. R. sativus sprout has recently been shown to have anti-tumor activity on human colon cancer cells, suggesting that it may have potential use in cancer prevention and treatment. The extent of this anti-tumor activity and its underlying mechanisms, however, remain to be investigated in other types of cancer cells. In this study, we showed that the MeOH extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In the present study, as part of our continuing efforts to discover compounds in Korean natural resources with antiproliferative activity against human lung cancer [21] , [22] , [23] , [24] , [25] , we explored the antiproliferative effects of KRG against human lung cancer cells. Six ginsenosides ( 1–6 ) were isolated from the active fraction through bioactivity-guided fractionation based on their cytotoxic activity and subsequent chemical investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, as part of our continuing efforts to discover compounds in Korean natural resources with antiproliferative activity against human lung cancer [21] , [22] , [23] , [24] , [25] , we explored the antiproliferative effects of KRG against human lung cancer cells. Six ginsenosides ( 1–6 ) were isolated from the active fraction through bioactivity-guided fractionation based on their cytotoxic activity and subsequent chemical investigation.…”
Section: Introductionmentioning
confidence: 99%
“…as well as promoting phosphorylation at Ser15 (Baek et al, 2017;Rajavel et al, 2018); in gastric cancer, apoptosis is induced through the influence on Bax, pro-caspase-3, and Bcl-2 (Zhao et al, 2009;Zhong et al, 2022). Similarly, in liver cancer HepG2 cells, both intrinsic and extrinsic apoptotic pathways are activated, involving death receptors and Bcl-2 (Anwar et al, 2020;Zhang et al, 2011).…”
Section: Anticancer Effects and Mechanisms Of β-Sitosterolmentioning
confidence: 99%
“…When it comes to apoptosis, β‐sitosterol functions through various mechanisms. For instance, in lung cancer A549 cells, β‐sitosterol triggers apoptosis via p53 regulation, affecting molecules such as p21 and p53 as well as promoting phosphorylation at Ser15 (Baek et al, 2017; Rajavel et al, 2018); in gastric cancer, apoptosis is induced through the influence on Bax, pro‐caspase‐3, and Bcl‐2 (Zhao et al, 2009; Zhong et al, 2022). Similarly, in liver cancer HepG2 cells, both intrinsic and extrinsic apoptotic pathways are activated, involving death receptors and Bcl‐2 (Anwar et al, 2020; Zhang et al, 2011).…”
Section: Anticancer Effects and Mechanisms Of β‐Sitosterolmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Baeka et al. indicated that SIT could effectively reduce the viability of p53-deficient human lung cancer Calu-6 cells ( 21 ).…”
Section: Induction Of Tumor Cell Apoptosis After Sit Interventionmentioning
confidence: 99%